PRINCIPLES OF PROFESSIONAL EDUCATION IN A MODERN SCHOOL AND THE CONCEPT OF “RELATED LABOR” G.S. SKOVORODA: COMPARATIVE-METHODOLOGICAL ANALYSIS (Pedagogy of Higher and Secondary Education, 2009)
This article is devoted to a comparative analysis of Gryhoriy Skovoroda concept of "affined labor" and bases of profile training in senior high school Skovoroda's concept is disclosed as a philosophical and methodological justification of importance of profile training in moders educational space.